One-part self-healing anticorrosive coatings via microencapsulation of reactive agents - Huang, Mingxing (2013)
Corrosion is a worldwide open issue and corrosion control has been one of the most important factors in the fields of materials design and application. Various traditional approaches have been developed and applied to address this problem. However, most of such methods are passive and lack of active response to damage events. Recently the concept of self-healing has been employed to develop anticorrosive coatings with different chemistries via microencapsulation. To date most of such coatings are based on two-part chemistries to trigger healing reaction, which increases manufacturing complexity and environmental concern. In this study, two novel reactive agents were adopted and successfully microencapsulated as self-healing additives to protective coating for active corrosion control upon damage events. The healing agents are reactive with water that is the essential media to facilitate corrosion process. Two self-healing anticorrosive coating systems were developed and comprehensively characterized. The first healing chemistry is based on a highly reactive liquid diisocyanate monomer, hexamethylene diisocyanate (HDI), which is encapsulated into polyurethane microcapsules through a facile interfacial polymerization reaction. The synthesized capsules are integrated into epoxy to prepare self-healing anticorrosive coatings. The HDI-filled microcapsules are characterized by different analytical techniques, and the influences of reaction variables such as reaction time, temperature, agitation rate, etc. on the resultant capsules are investigated. The shelf life of the microcapsules in different environment is studied, and it is found that the barrier property of the microcapsule is yet to be improved. The corrosion protection performance of the prepared HDI microcapsules based self-healing coating is evaluated by an accelerated salt immersion test and a comprehensive salt spray test following industrial standard. DC electrochemical test and electrochemical impedance study are also performed to quantitatively assess the self-healing and anticorrosive property of the coatings. The test results reveal that the HDI based coatings provide excellent corrosion protection upon manual scratches towards metal substrates via a self-healing mechanism. The second self-healing chemistry is based on 1H,1H’,2H,2H’-perfluorooctyltriethoxy silane (POTS), a commercial organic silane. In this study, it has been encapsulated into poly(urea-formaldehyde) microcapsules through an in situ polymerization reaction. The produced microcapsules are comprehensively characterized and the influences of the reaction parameters on the resultant microcapsules are investigated. The microcapsules show good environmental stability. The synthesized POTS-filled microcapsules are used to develop self-healing coatings, and the excellent corrosion protection ability of the prepared coatings to metal substrate is demonstrated by different test methods. The anticorrosive mechanisms of the new microcapsule-based coatings via self-healing reaction are discussed. The healing or sealing performance is directly related to the availability of healing agents. Based on a simplified damage model, the influence of the variables on the crack sealing performance of the prepared coating is discussed, and it is found that the amount of available healing agents in a crack is proportional to the microcapsules size, weight fraction of microcapsules in coating and the coating thickness, which is agreeable with the experimental observation. In addition, the anticorrosive mechanism is briefly discussed for the intact coating where self-healing microcapsules serve as numerous reservoirs to trap and react with the diffused water and thus to retard the corrosion process.